Quality of Life in Patients with Renal Failure Undergoing Hemodialysis - Haerani Rasyid; Hasyim Kasim; St. Rabiul Zatalia; Jerry Sampebuntu (Interna Publishing, 2022)
A good quality of life is one of the many indicators that determine the success of hemodialysis (HD) therapy. Factors that significantly affect the quality of life of patients with renal failure who undergo HD include sociodemographic condition, mental state (depression), severity of kidney disease, accompanying disorders, HD duration, non-adherence towards prescribed medication and nutritional problems. Among said factors, the metabolic and nutritional disorder commonly known as protein energy wasting (PEW), plays an important role in the clinical course of renal failure patients. The aim of nutrition management in patients with renal failure is to slow down the progression of kidney disease, improve quality of life, and reduce cardiovascular morbidity and mortality.